1988
DOI: 10.1007/bf00248500
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the responses of cat dorsal horn neurons to noxious skin heating by stimulation in medial or lateral medullary reticular formation

Abstract: Responses of single lumbar dorsal horn units to noxious radiant heating (50 degrees C, 10 s) of glabrous footpad skin were recorded in cats anesthetized with sodium pentobarbital and 70% nitrous oxide. The heat-evoked responses of 37/40 units were reduced during electrical stimulation (100 ms trains, 100 Hz, 3/s, 25-600 microA) in the medullary nucleus raphe magnus (NRM) and/or in laterally adjacent regions of the medullary reticular formation (MRF). Inhibition was elicited by stimulation in widespread areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In keeping with such results, electrical stimulation in Gi can also inhibit nociceptive activity in spinal and trigeminal neurones (Zorman et al 1981;Dostrovsky, Shah & Gray, 1983;Pretel, Guinan & Cartens, 1988;Yezierski, 1990). Finally, anatomical data are compatible with the participation of this structure in spino-bulbo-spinal loops since it receives afferents from, and projects to, the spinal cord (Basbaum, Clanton & Fields, 1978;Zemlan, Behbehani & Beckstead, 1984;Matsuyama, Ohta & Mori, 1988).…”
Section: Discussionmentioning
confidence: 73%
“…In keeping with such results, electrical stimulation in Gi can also inhibit nociceptive activity in spinal and trigeminal neurones (Zorman et al 1981;Dostrovsky, Shah & Gray, 1983;Pretel, Guinan & Cartens, 1988;Yezierski, 1990). Finally, anatomical data are compatible with the participation of this structure in spino-bulbo-spinal loops since it receives afferents from, and projects to, the spinal cord (Basbaum, Clanton & Fields, 1978;Zemlan, Behbehani & Beckstead, 1984;Matsuyama, Ohta & Mori, 1988).…”
Section: Discussionmentioning
confidence: 73%
“…Histological studies showed that NRL neurons have complex input-output relations from-to various parts of the central nervous system (Janss and Gebhart, 1987, Pretel, at al., 1988, Murphy and Behbehani, 1993a, 1993b. It is thought that important descending analgesic mechanisms underlying acupuncture analgesia work through connections from NRL to NRM and from NRL to SC.…”
Section: Introductionmentioning
confidence: 99%